HUBUNGAN ANTARA KOMPETENSI SOSIAL DAN KEPERCAYAAN DIRI PADA SISWA - Dina Hazadiyah; N. Kardinah; Imam Sunardi (Fakultas Psikologi, Universitas Islam Negeri (UIN) Sunan Gunung Djati Bandung, 2012)
This research used non-experimental approach with correlational technique studying whether social competency correlated with self-esteem. Purposive sampling were taken from 343 students of grade X Madrasah Aliyah Negeri 2 Kota Bandung. Data were collected using social competency scale and self-esteem scale. Result shows that there is significant correlation between social competency and self-esteem with cooficient correlation 0,565 at significancy level (0,000). High social competency produce highself-esteem whereas low social competency result low self-esteem.